Catholic education in Europe, education pluralism, and public funding. Issue 1 (2nd January 2023) - Wodon, Quentin
Abstract : According to Church statistics, 6.9 million children were enrolled in Catholic primary and secondary schools in Europe. Enrolment has remained relatively stable over the last 40 years in comparison to other regions of the world, contributing to education pluralism. This may be in part because in many countries, Catholic and private schools benefit from state funding, which helps in reducing out-of-pocket costs for parents to send their children to the schools. At the same time, public funding for private schools, including Catholic schools, often remains below the level of funding for public schools. This paper discusses enrolment trends in Catholic schools over time, compares the level of public funding for private and public schools, and looks at the relationships (or lack thereof) between such funding and enrolment in Catholic and private schools.